Pengaruh TATO, ROA, CR, dan EPS Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2016 – 2019 - Yessi Panjaitan; Sarah Sitanggang; Keumala Hayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study is to determine the Total Asset Turnover, Return On Asset, Curent Ratio, and Earning Per Share on stock prices of manufacturing companies on the IDX. Any data required is official data from the annual financial report that comes from the IDX. The method of sampling using purpose sampling method. There is a test used consisting of the classical assumption test which parts of the normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, panel data regression test, coefficient (R2), hypothesis (T test), hypothesis (F test). Fundamental factors (TATO, ROA, CR, EPS) together have a 70.6% impact on stock prices, the remaining 29.4% are influenced by other variables. The results of the research are: (1) there is no significant effect of Total Asset Turnover, Return On Asset, Current Ratio on stock prices. (2) Significant influence of Earning Per Share on stock prices. (3) the effect of TATO, ROA, CR, EPS simultaneously on stock prices. Keywords: Current Ratio; Earning Per Share; Return On Asset; stock price; Total AssetTurnover